2002
DOI: 10.1253/circj.66.902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heart-Rate Turbulence as a New Prognostic Marker in Patients With Chronic Heart Failure.

Abstract: The significance of heart-rate turbulence (HRT) in patients with chronic heart failure (CHF) was evaluated to examine whether it is sensitive to the risk of ventricular tachycardia (VT). HRT is reported to predict the prognosis after myocardial infarction (MI), but its prognostic value in patients with CHF remains unknown. HRT was measured in 50 CHF patients (left ventricular ejection fraction <50% and/or left ventricular end-diastolic diameter >55 mm, 34 cardiomyopathy, 16 post-MI) and 21 patients without obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 21 publications
(23 reference statements)
7
61
2
2
Order By: Relevance
“…HRT is highly correlated with spontaneous baroreflex sensitivity and it may be used instead of baroreflex sensitivity as a new diagnostic method (21). It is proven that HRT also predicts mortality and sudden cardiac death in various cardiac abnormalities like postmyocardial infarction period (13), after coronary artery bypass grafting surgery (22) and in chronic heart failure (23). In addition, HRT predicts alterations of cardiac autonomic function in diabetes mellitus (24) and hyperthyroidism (25).…”
Section: Discussionmentioning
confidence: 99%
“…HRT is highly correlated with spontaneous baroreflex sensitivity and it may be used instead of baroreflex sensitivity as a new diagnostic method (21). It is proven that HRT also predicts mortality and sudden cardiac death in various cardiac abnormalities like postmyocardial infarction period (13), after coronary artery bypass grafting surgery (22) and in chronic heart failure (23). In addition, HRT predicts alterations of cardiac autonomic function in diabetes mellitus (24) and hyperthyroidism (25).…”
Section: Discussionmentioning
confidence: 99%
“…23 Several studies have shown that reduced heart rate variability (HRV), determined from 24-h ambulatory electrocardiographic (ECG) recordings, is associated with a greater risk for ventricular fibrillation and poor prognosis in patients with CHF. [24][25][26][27] Therefore, we prospectively investigated the effects of thermal therapy on cardiac arrhythmias and HRV in patients with CHF.…”
mentioning
confidence: 99%
“…15 HRT is defined as the sinus rhythm cycle-length fluctuation after isolated premature ventricular beats. 16 HRT evaluation has been deemed appropriate for risk estimation after acute myocardial infarction 17 and as a prognostic evaluator for heart failure 18 and other pathological conditions. 16 Autonomic cardiac functions in OSA patients have been the focus of attention for researchers.…”
Section: Introductionmentioning
confidence: 99%